Faktor-Faktor Yang Berhubungan Dengan Unsafe Action Pada Pekerja Bagian Produksi PT Batanghari Barisan Tahun 2021 - Yusfita , Ermi (CV. ITTC INDONESIA, 2023)
Based on data from PT Batanghari Barisan in 2020, the number of work accidents were 14 cases. One of the factors that influence work accidents is unsafe action. The purpose of this study was to determine the relationship between knowledge, attitudes, physical environment and physical abilities with unsafe acts on employees of the production division of PT Batanghari Barisan in 2021.The type of research used in this research was analytic with a cross sectional design, which was carried out in July - August 2021. The populations in this study were all workers in the production division of PT Batanghari Barisan as many as 190 people. Samples were taken by proportional random sampling method as many as 142 people. Data were collected through direct interviews using questionnaires. Then it was processed with SPSS and analyzed by Chi- square statistical test with a degree of significance (α= 0.05).The results showed that workers who experienced unsafe action were 59.9%, workers with less knowledge were 49.3%, workers with risky attitudes were 51.4%, workers with risky physical environment were 52.1% and workers with risky physical abilities were 52.1%%. Factors related to unsafe action were knowledge (p= 0.01), attitude (p= 0.00), physical environment (p= 0.024), and physical ability (p=0.00).Based on the results of this study, it can be concluded that all independent variables were related to variables. In order to minimize unsafe action, it is recommended that the company be able to regulate the policy of rest periods, provide personal protective equipment, facilitate training activities and adjust the conditions of workers with workers' equipment.